2003
DOI: 10.1097/00001756-200312190-00020
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive effects of neuromedin U microinjected into the cardiovascular-related region of the rat nucleus tractus solitarius

Abstract: Neuromedin U (NMU) is a brain-gut peptide with potent contractile effects on the uterus and smooth muscle. Intracerebroventricular injection of NMU reportedly decreased food intake and body-weight gain in the rat. We evaluated the effects of NMU delivered by microinjection into the rat nucleus tractus solitarius (NTS) on cardiovascular responses. At the concentrations used (5, 10 or 50 pmol), the intra-NTS injection of NMU in artificial cerebrospinal fluid produced a significant reduction in both the mean arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…administration (8,55,57,58 ), suggesting that although NmU might indeed regulate these phenomena centrally, further work is needed before its true role is elucidated. However, more recent reports appear to indicate that the prevalent effect of central NmU administration is to increase blood pressure through regulation of sympathetic activity (59 -62 ).…”
Section: Blood Pressure and Blood Flowmentioning
confidence: 99%
“…administration (8,55,57,58 ), suggesting that although NmU might indeed regulate these phenomena centrally, further work is needed before its true role is elucidated. However, more recent reports appear to indicate that the prevalent effect of central NmU administration is to increase blood pressure through regulation of sympathetic activity (59 -62 ).…”
Section: Blood Pressure and Blood Flowmentioning
confidence: 99%
“…Tsubota et al. [53] reported hypotensive effects of NmU when administered in the nucleus tractus solitarus of rat. NmU also affects regional blood flow especially the splanchnic circulation.…”
Section: Blood Pressure and Regional Blood Flowmentioning
confidence: 99%
“…NmU increases sympathetic activityconsistent with its localization in the paraventricular nuclei (PVN) of the hypothalamus. Tsubota et al [53] reported hypotensive effects of NmU when administered in the nucleus tractus solitarus of rat. NmU also affects regional blood flow especially the splanchnic circulation.…”
Section: B L O O D P R E S S U R E a N D R E G I O N A L B L O O D F mentioning
confidence: 99%
“…Early characterizations of NmU revealed its potent contractile activity in the rat uterus (6, 7) which were followed by experiments demonstrating contraction of smooth muscle of many organs (8,9). Several studies indicate that NmU also plays a role in energy homeostasis, (10 -13) regulation of blood pressure (14,15), and nociception (16,17). Taken together, these reports indicate a wide variety of functions for NmU and suggest potential mechanisms by which release of signaling molecules from neurons can mediate processes both within the CNS and in peripheral tissues.…”
Section: T Ype-2 Th (Th2) Cells Are Cd4mentioning
confidence: 99%